Determination of factors in pepper genotypes for ornamentation (Research, Society and Development, 2020)
The present work had as main objective to use factor analysis to describe the structure of variability of characteristics considered commercially important in ornamental pepper, aiming to summarize the information contained in such variables in a smaller number of latent variables or factors. For that, 12 quantitative traits were evaluated in 29 pepper genotypes (Capsicum annuum). Of the factors created, 3 presented practical interpretation, grouping a total of 12 variables into factors related to “fruit quality” (8 variables), “plant size” (2 variables) and “plant architecture” (2 variables).